Ascorbic acid, pigments, anti-nutritional factors, and nutraceutical potential of Anacardium occidentale fruits as affected by temperature - Roger Dakuyo; Kiessoun Konaté; Kabakdé Kaboré; Abdoudramane Sanou; Frédéric Anderson Konkobo; David Bazié; Hemayoro Sama; Mamoudou Hama Dicko (International Journal of Food Properties, 2023)
Cashew tree has two parts of food industry and nutrition interest, i.e the nut and the juicy apple. This study aimed to carry out a phytochemical characterization, determine the antioxidant properties and evaluate the influence of temperature on the phytonutrient composition of cashew fruits. The contents of ascorbic acids, phytates, and tannins, of various pigments were determined. Antioxidant activities were determined by four methods using standard methods. The apples presented the best antioxidant activities for FRAP, SOD, and LPO 98.54 ± 5.48, 834.12 ± 13.47, and 84.9 ± 4.15, respectively; while walnuts showed the best antioxidant activities for free radical scavenging which was 26.14 ± 3.21. Tannin, phytate, and anthocyanin contents decreased by more than 50% when increasing temperatures between 50 and 100°C. Ascorbic acid tends to disappear completely in fruit at temperatures of 100°C. Extractable lycopene increased by about 25% with increasing temperature. β-carotene was found to be insensitive to temperature increase. These results provide valuable information that can help in the control of cashew fruit processing in the food industry. They also provide important information on the nutraceutical potential of cashew fruit.